Synthesis, 3D-QSAR and Molecular Docking Study of Nopol-Based 1,2,4-Triazole-Thioether Compounds as Potential Antifungal Agents - Wang, Xiu; Duan, Wengui; Lin, Guishan; Li, Baoyu; Chen, Ming; Lei, Fuhou (Frontiers in Chemistry, 2021)
Cytochrome bc1 complex is an important component of cellular respiratory chain, and it is also an important target enzyme to inhibit the growth of plant pathogens. Using cytochrome bc1 complex as the target enzyme, twenty-three novel nopol-based 1,2,4-triazole-thioether compounds were designed and synthesized from natural preponderant resource β-pinene, and their structures were confirmed by FT-IR, NMR, ESI-MS and elemental analysis. The in vitro antifungal activity of the target compounds 5a-5w was preliminarily evaluated against eight plant pathogens at the concentration of 50 µg/mL. The bioassay results showed that the target compounds exhibited the best antifungal activity against Physalospora piricola, in which compounds 5b (R= o-CH3 Ph), 5e (R= o-OCH3 Ph), 5h (R= o-F Ph), 5m (R= o-Br Ph), 5o (R= m,m-OCH3 Ph), and 5r (R= p-OH Ph) had inhibition rates of 91.4%, 83.3%, 86.7%, 83.8%, 91.4% and 87.3%, respectively, much better than that of the positive control chlorothalonil. Also, compound 5a (R= Ph) had inhibition rate of 87.9% against Rhizoeotnia solani, and compound 5b (R= o-CH3 Ph) had inhibition rates of 87.6% and 89% against Bipolaris maydis and Colleterichum orbicala, respectively. In order to develop novel and promising antifungal compounds against P. piricola, the analysis of three-dimensional quantitative structure-activity relationship (3D-QSAR) was carried out using the CoMFA method on the basis of their antifungal activity data, and a reasonable and effective 3D-QSAR model (r2= 0.952, q2= 0.575) has been established. In addition, the theoretical study of molecular docking revealed that the target compounds could bind to and interact with the site of cytochrome bc1 complex.